Pengaruh Budaya Organisasi, Modal Intelektual, dan Perilaku Inovatif Terhadap Kinerja Pemimpin Jurusan di Universitas Negeri Medan - Purba, Sukarman (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2009)
The Ã‚Â objective Ã‚Â of Ã‚Â this Ã‚Â research Ã‚Â is Ã‚Â to Ã‚Â obtain Ã‚Â information Ã‚Â concerning Ã‚Â the Ã‚Â effect of Ã‚Â organizationalÃ‚Â culture, Ã‚Â intellectual Ã‚Â capital, Ã‚Â innovative Ã‚Â behavior, Ã‚Â on Department Ã‚Â chairmanÃ¢â‚¬â„¢s Ã‚Â performance. Ã‚Â TheÃ‚Â research Ã‚Â was Ã‚Â carried Ã‚Â out Ã‚Â in Ã‚Â 2005 with Ã‚Â sample Ã‚Â of Ã‚Â 40, Ã‚Â selected Ã‚Â randomly Ã‚Â and the data Ã‚Â has Ã‚Â beenÃ‚Â analyzed by path Ã‚Â analysis Ã‚Â after Ã‚Â all Ã‚Â variables Ã‚Â put Ã‚Â into Ã‚Â the Ã‚Â correlation Ã‚Â matrix. Ã‚Â Ã‚Â The finding of Ã‚Â theÃ‚Â research Ã‚Â shows Ã‚Â that Ã‚Â Department Ã‚Â chairmanÃ¢â‚¬â„¢s Ã‚Â performance Ã‚Â is Ã‚Â affected directly by OrganizationalÃ‚Â culture, Intellectual capital, and Innovative behavior. Based on those findings it could be concluded thatÃ‚Â any changing or variation which occurred at Department chairmanÃ¢â‚¬â„¢s performance might have been effectedÃ‚Â by Organizational Ã‚Â culture, Ã‚Â Intellectual Ã‚Â capital, Ã‚Â and Ã‚Â Innovative Ã‚Â behavior. Therefore, Ã‚Â in Ã‚Â managingÃ‚Â Department chairmanÃ¢â‚¬â„¢s performance, organizational culture, intellectual capital, and innovativeÃ‚Â behavior should be put into strategic planning of human resources development at UniversitasÃ‚Â Negeri Ã‚Â Medan, Ã‚Â however other Ã‚Â variables Ã‚Â are Ã‚Â necessary Ã‚Â to Ã‚Â be Ã‚Â taken Ã‚Â into Ã‚Â account Ã‚Â by Ã‚Â next Ã‚Â performance Ã‚Â Ã‚Â research.